Clinical trials evaluating potential therapies for light chain (AL) amyloidosis. (3rd August 2017) - Muchtar, Eli; Gertz, Morie A.
ABSTRACT: Introduction : The field of systemic amyloidosis is experiencing major advances in diagnostic and prognostic methods coupled with a growing availability in treatment options. Areas covered : Treatment of AL amyloidosis traditionally targeted the clonal plasma cells, in order to block further production of amyloidogenic light chains. Currently, a research focus is placed on targeting the already formed amyloid deposits using monoclonal antibodies against epitopes on such deposits. Encouraging results were obtained from the three investigated antibodies: NEOD001, 11-1F4 and anti-SAP, but further validation is required before these antibodies can be commercialized. In this paper, we review the current active clinical research in AL amyloidosis, which includes the monoclonal antibodies targeting amyloid deposits, daratumumab, Venetoclax, doxycycline, green tea, pomalidomide, carfilzomib and ixazomib. Expert opinion : Monoclonal antibodies, targeting either the amyloid deposits or the plasma cell compartment will likely be integrated into routine treatment practice given their encouraging results and minimal toxicity in the fragile population of AL amyloidosis. Other therapeutic options hold promise to the field as well, but toxicity will likely challenge their routine use. Early recognition remains the best option for outcome enhancement.